2005
DOI: 10.1029/2005gl024461
|View full text |Cite
|
Sign up to set email alerts
|

Electron tomography of nanoparticle clusters: Implications for atmospheric lifetimes and radiative forcing of soot

Abstract: [1] Nanoparticles are ubiquitous in nature. Their large surface areas and consequent chemical reactivity typically result in their aggregation into clusters. Their chemical and physical properties depend on cluster shapes, which are commonly complex and unknown. This is the first application of electron tomography with a transmission electron microscope to quantitatively determine the threedimensional (3D) shapes, volumes, and surface areas of nanoparticle clusters. We use soot (black carbon, BC) nanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 29 publications
4
85
1
Order By: Relevance
“…2. Consistent with other authors (Adachi et al, 2007;van Poppel et al, 2005;Kis et al, 2006), primary particles are found with a size of about 30-40 nm aggregated in chains. Inspection by eye does not reveal changes in aggregation of the particles, which is supported by the evaluation of the fractal dimension revealing 1.84 (±0.03) for fresh and 1.85 (±0.05) for processed particles, respectively.…”
Section: Particle Morphology and Size Distributionsupporting
confidence: 81%
“…2. Consistent with other authors (Adachi et al, 2007;van Poppel et al, 2005;Kis et al, 2006), primary particles are found with a size of about 30-40 nm aggregated in chains. Inspection by eye does not reveal changes in aggregation of the particles, which is supported by the evaluation of the fractal dimension revealing 1.84 (±0.03) for fresh and 1.85 (±0.05) for processed particles, respectively.…”
Section: Particle Morphology and Size Distributionsupporting
confidence: 81%
“…13a and c). Most of the biological particles were likely spores or conidia of fungi (Wittmaack et al, 2005), but the detailed classification of these particles was beyond the scope of this work. There were also several angular C-rich particles without clearly characteristic morphology of biological particles ( Fig.…”
Section: Biological Particles and C-rich Fragmentsmentioning
confidence: 99%
“…In Finland, anthropogenic emissions of particles and their precursor gases are low (EMEP, 2001(EMEP, , 2002, and most of the PM 2.5 mass originates from long-range transport (Pakkanen et al, 2001;Vallius et al, 2003;Karppinen et al, 2004). In general, PM 2.5 concentrations are also low, the annual mean PM 2.5 concentration being only 5.8 µg m −3 at the rural station of Hyytiälä in southern Finland (Laakso et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Visual scanning is rapid and can be used to select a relatively small number of particles that appear to be representative and, if appropriate, can then be subjected to detailed studies using electron tomography to determine their 3D shapes (van Poppel et al 2005;Adachi et al 2007). Morphology and mixing state strongly influence the scattering cross-sections of ns-soot.…”
Section: Associated Materials Coating Embeddingmentioning
confidence: 99%